White rice vinegar improves pancreatic beta-cell function and fatty liver in streptozotocin-induced diabetic rats - Gu, Xuemei; Zhao, Hai-Lu; Sui, Yi; Guan, Jing; Chan, Juliana C. N.; Tong, Peter C. Y. (Acta diabetologica, 2012)
Vinegar is a traditional remedy for ailments including diabetes. This study was conducted to investigate the beneficial effects of vinegar in streptozotocin (STZ)-induced diabetic rats. STZ-induced diabetic rats were orally administered with white rice vinegar (WRV, 2 ml/kg body weight per day, n = 6) or with an equal volume of drinking water ( n = 6) for 1 month. Fasting and random blood glucose was measured from tail vein samples. Body weight, 24-h food and water intake were monitored 1 week and 1 month after STZ injection. Fasting serum insulin concentrations were assayed using ELISA. Pancreatic beta- and alpha-cell proportions were measured using immunofluorescence microscopy. Periodic acid Schiff staining was performed to access glycogen contents and histological changes in liver tissues. Compared with control animals, the WRV-treated rats had less weight loss, lower fasting and random blood glucose, higher fasting serum insulin and higher beta-cell proportion. The WRV treatment also improved fatty changes and glycogen storages in the liver of STZ rats. Oral intake of WRV improved fasting hyperglycemia and body weight loss through attenuating insulin deficiency, pancreatic beta-cell deficit, and hepatic glycogen depletion and fatty changes in STZ-induced diabetic rats.